Intermittent Cyanosis Years after a Mustard Repair for Dextro-Transposition of the Great Arteries - Saraf, Anita (Texas Heart Institute, 2012)
A 28-year-old woman, who as an infant had undergone the Mustard atrial switch procedure for dextro-transposition of the great arteries, presented with a baffle leak and consequent intermittent cyanosis. In addition, an occlusive thrombus had formed in the systemic venous baffle after a failed attempt to remove infected pacemaker leads. Corrective surgery was successful. In addition to the case of our patient, we discuss long-term sequelae of the atrial switch procedure that present challenges in patient care.